Mobility as a Service: Insights from pilot studies across different Italian settings - Italo Meloni; Giuseppe Musolino; Francesco Piras; Corrado Rindone; Francesco Russo; Eleonora Sottile; Antonino Vitetta (Transportation Engineering)
Mobility as a Service (MaaS) has been tested in numerous cities and enables users to travel within an integrated system of collective and shared transport services, with a single travel package or bundle, giving them the ability to plan, book and pay for a trip using a unique technological platform. At this stage of the MaaS system experimentation, a detailed analysis on a small scale enables, through the understanding of the mechanisms governing travel choices, the planning of a MaaS service on a large scale that has the right flexibility to adapt to different territorial contexts. The paper reports the main findings of a study carried out as part of a national research project funded by the Italian Ministry of University and Research. Within this project, evaluation methodologies were developed (Technology Acceptance Model, Revealed Preferences and Intended Preference surveys), pilot surveys were conducted on samples of potential users, and the results were analysed and compared to assess the potential activation of a MaaS and to estimate its impacts on mobility.Two pilot experiments and an extended test, with a sample of almost 200 users, were carried out in different territorial contexts in Italy: the metropolitan areas of Reggio Calabria and Messina, the extra-urban area of Gioia Tauro and the urban area of the metropolitan city of Cagliari. The activities should be regarded as preliminary and indispensable stage for the design of more extensive investigations, as well as for the planning of a possible MaaS system in the areas examined.